Linker insertion mutations in the human immunodeficiency virus type 1 gag gene: effects on virion particle assembly, release, and infectivity. - Reicin, A S (1995)
The phenotypes of a series of mutant human immunodeficiency virus type 1 proviruses with linker insertion and deletion mutations within the gag coding region were characterized. These mutants were tested for their ability to make and release viral particles in COS7 cells and for their viability in vivo. Of the 12 mutant proviruses, 4 did not make extracellular virion particles when transfected into COS7 cells. All four of these mutants had mutations in the C-terminal domain of CA. These mutants appeared to have defects both in the ability to accumulate high-molecular-weight intracellular structures containing Gag and Pol products and in the ability to release virion particles. Seven of the mutant proviruses retained the ability to make, release, and process virion particles from COS7 cells. These particles contained the Env glycoprotein, viral genomic RNA, and the mature products of the Gag and Gag-Pol polyproteins, yet they were noninfectious or poorly infectious. The defect in these mutants appears to be in one of the early steps of the viral life cycle. Thus, multiple regions throughout Gag appear to be important in mediating the early steps of the viral life cycle.